Suction Drainage for Anastomotic Leakage After Ivor Lewis Esophagectomy. Issue 1 (21st February 2023) - Lubbers, Merel; van Det, Marc J.; Crull, David; van der Linden, Andries; Vrij, Anton A.; Kouwenhoven, Ewout A.
Abstract : Background: Anastomotic leakage is one of the most life-threatening complications after Ivor Lewis esophagectomy (ILE), with various treatment strategies. Endoscopic techniques are emerging as a less invasive alternative to surgery. Among the current endoscopic techniques, a single placement of an endoluminal nasogastric tube inside the cavity with controlled suction drainage (SD) seems to be an attractive option. The aim of this study was to evaluate the efficacy of SD as treatment for anastomotic leakage after ILE. Methods: This retrospective analysis was performed among patients who underwent ILE in a high-volume esophageal cancer center in the Netherlands. Patients with an anastomotic leakage that received SD as primary treatment were selected. A nasogastric tube was endoscopically placed into the cavity of the leakage for controlled suction with 15 mm Hg. Results: A total of 34 patients received SD and was successful in 26 patients (77%). Seven patients (21%) developed empyema despite the SD for which additional video-assisted thoracoscopic surgery was performed. Mortality was 5.9% (2 patients) and median intensive care unit and hospital stay were 3 days (1 to 9) and 25 days (14 to 43), respectively. The median time to closure of the leak was 41 days (23 to 65). A total of 16 patients underwent home treatment for a median of 23 (14 to 42) days. Conclusions: Controlled SD seems to be an effective treatment for anastomotic leakage after ILE. This therapy can safely and effectively be completed in an ambulant, outpatient setting.